2015
DOI: 10.1097/01.j.pain.0000460330.56256.25
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and the environment affect the relationship between depression and low back pain

Abstract: Although the co-occurrence of low back pain (LBP) and depression is common, the nature of this association remains unclear. We aimed to investigate whether symptoms of depression are associated with LBP after adjusting for various confounders, including genetics. We used cross-sectional data from 2148 twins from the Murcia Twin Registry, Spain. All twins answered questions about lifetime prevalence of LBP (outcome variable) and symptoms of depression, collected through two instruments, deriving 3 measures: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 37 publications
5
41
0
Order By: Relevance
“…In light of the moderate to large effects of genetic factors on low back pain (Ferreira et al, 2013) and depression (Sullivan et al, 2000), our research group has recently investigated the relationship between low back pain and symptoms of depression and anxiety while accounting for genetic and environmental factors by employing a co-twin case-control design (Pinheiro et al, 2015a, Pinheiro et al, 2016. The findings from…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…In light of the moderate to large effects of genetic factors on low back pain (Ferreira et al, 2013) and depression (Sullivan et al, 2000), our research group has recently investigated the relationship between low back pain and symptoms of depression and anxiety while accounting for genetic and environmental factors by employing a co-twin case-control design (Pinheiro et al, 2015a, Pinheiro et al, 2016. The findings from…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Population-based studies have shown that the prevalence of widespread pain increases with age, peaking in the seventh and eighth decades (20,21). Recently, it has been show that genetics also played a role in the development of LBP (1,22,23).…”
Section: Evidence-based Medicinementioning
confidence: 99%
“…For instance, we observed strong positive genetic correlations between BP and depression related phenotypes, and between BP and obesity-related traits. These traits are known to often co-occur with BP and twin studies have suggested that they share underlying genetic factors 17 , with similar genetic correlations also seen for other pain phenotypes. [55][56][57] Our results confirm a recent twin report of genetic correlation of sleep disturbance with BP.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, not only is there a phenotypic association between LDD and LBP but a genetic correlation between the two has been reported in twin studies (11%-13%) 10,16 , suggestive of shared genetic background. Twin studies have demonstrated that BP also shares an underlying genetic predisposition with several of its risk factors including depression and anxiety 17 , educational attainment 18 , obesity 19 as well as with other pain conditions such as chronic widespread musculoskeletal pain 20 .…”
mentioning
confidence: 99%